Efektivitas Model Pembelajaran SAVI dalam Mata Pelajaran IPA di Kelas V Sekolah Dasar - Siti Nur Afifah; Septi Budi Sartika (Elementar : Jurnal Pendidikan Dasar, 2022)
This study aims to describe the effectiveness of the SAVI learning model in science subjects in grade 5 of SD. Data collection techniques using observation, tests, and questionnaires. The results showed that: (1) The teacher's ability to manage science learning using the SAVI learning model was categorized in good classification. With a percentage of 100% at the second meeting and third and 90% at the first meeting. (2) Student activity in science learning with the SAVI learning model, which is in very good classification with a percentage of 100%. (3) the academic response is classified as very good with an average score of 90%. (4) the results of student observations in science learning after the SAVI model was applied to grade 5 students of SD were categorized in very good and effective classification. Based on the calculation of N-gain with a value of 71.3659 included in the high category which is in the interval 0.7≥g <1. Based on the results of the study, it can be concluded that the effectiveness of the SAVI learning model in science learning for grade 5 SD can be said to be effective.